Notes on an Implementation of Sugiyama's Scheme - Nachmanson, Lev (2006)
These technical notes are comments on my work on GLEE, Graph Layout Execution Engine. GLEE is a library developed inside Microsoft Research and is written in the C# language. The library has quite a few users inside of Microsoft. GLEE implements Sugiyama's scheme of layout for directed graphs, or so-called layered layout. The paper describes in more detail efficient coding of adjacent vertex swaps and spline routing, where the latter is based on the b-spline in a channel approach by Lutterkort and Peters.